Advances in eggshell membrane separation and solubilization technologies - Han, Chunhao; Chen, Yifan; Shi, Lei; Chen, Hui; Li, Lanhui; Ning, Zhonghua; Zeng, Dan; Wang, Dehe (Frontiers in Veterinary Science, 2023)
Eggshell membranes (ESM) contain 90% protein, 3% lipids, 2% sugars, and small amounts of minerals such as calcium and magnesium. Of the 90% of proteins present, 472 proteins species have been identified. ESM provide the initial mineralization platform for eggshell formation, and can be used for to produce adsorbents, cosmetics, and medical products because of their special physical structure and chemical composition. The special physical structure of the eggshell membrane, with disulfide bonds between and within the protein molecules and the cross-linking of lysine-derived and heterochain chains between the eggshell membrane, makes the membrane very difficult to dissolve, with a maximum solubility rate of only 62%. Also, the insolubility of ESM limits its development and use also any related research. Based on the physical structure and chemical composition of the eggshell membrane, this paper reviews the latest research on eggshell membrane separation and membrane protein solubilization to provide a reference for promoting the separation, dissolution, and rational development and use of the avian eggshell membrane.